Excitation of own oscillations in semiconductor components of radio products under the exposure of third-party electromagnetic radiation - Serkov, Aleksandr; Breslavets, Vitalii; Breslavets, Juliya; Yakovenko, Igor (Національний технічний університет "Харківський політехнічний інститут", 2022)
The subject matter is the processes of analysis and mechanisms of interaction of EMP-induced currents and voltages with the processes characterizing the functional purpose of radio products, is usually carried out within the framework of the theory of distributed circuits. The presented approach makes it possible to evaluate the performance criteria in general (for example, to evaluate the critical energy characterizing a thermal breakdown), however, issues related to the determination of various types of electromagnetic interactions that occur directly in the components of a product under the influence of EMR remain open. The aim is the possibility of setting up theoretical and experimental studies based on the proposed calculation model for excitation of natural vibrations of a semiconductor structure (exponential growth of amplitude). The parameters of a third-party pulsed electromagnetic field, induced currents and characteristics of semiconductor devices have been established within which the regime of amplification of natural vibrations of a semiconductor structure is observed. The objectives are: mechanisms of interaction of induced currents with surface vibrations of semiconductor components of a radio product under the influence of pulsed electromagnetic radiation. The methods used are: methods of the theory of small perturbations in determining the spectrum of natural oscillations of the system - currents induced by electromagnetic radiation and natural oscillations of the components of the radio product. The following results are obtained: The mechanisms for the appearance of reversible failures of semiconductor components of radio products under the influence of third-party pulsed electromagnetic fields are determined. It has been established that the presence of a current induced by external radiation leads to the establishment of a mode of amplification of natural oscillations of semiconductor components of a radio product (reversible failures). Conclusion. Quantitative estimates of amplification (generation) modes of oscillations of semiconductor devices, distorting their performance depending on the parameters of external electromagnetic influence, allows developing mechanisms for electromagnetic compatibility of microwave radio products. A comparative analysis of the calculated data obtained in the work can be used in the manufacture of radio devices operating in the millimeter and submillimeter range (amplifiers, generators and frequency converters).

Предметом дослідження є процес аналізу механізмів взаємодії наведених ЕМІ струмів і напруги з процесами, що характеризують функціональне призначення радіовиробів, зазвичай проводиться в рамках теорії ланцюгів з розподіленими параметрами. Представлений підхід дозволяє оцінити критерії працездатності в цілому (наприклад оцінити критичну енергію, що характеризує тепловий пробій), проте питання пов'язані з визначенням різного роду електромагнітних взаємодій, що протікають безпосередньо в комплектуючих вироби при впливі ЕМІ залишаються відкритими. Метою дослідження є можливість постановки теоретичних та експериментальних досліджень на основі запропонованої розрахункової моделі порушення власних коливань напівпровідникової структури (експоненційного зростання амплітуди). Встановлено параметри стороннього імпульсного електромагнітного поля, наведених струмів та характеристик напівпровідникових приладів у межах яких спостерігається режим посилення власних коливань напівпровідникової структури. Цілі такі: механізми взаємодії наведених струмів з поверхневими коливаннями напівпровідникових комплектуючих радіовиробу за умов впливу імпульсного електромагнітного випромінювання. Методи, що застосовувались при дослідженні: методи теорії малих обурень щодо спектру власних коливань системи - наведені електромагнітним випромінюванням струми і власні коливань комплектуючих радіовиробів. Отримано такі результати: Визначено механізми появи оборотних відмов виробів напівпровідникових комплектуючих радіовиробів за умов впливу сторонніх імпульсних електромагнітних полів. Встановлено, що наявність наведеного зовнішнім випромінюванням струму призводить до встановлення режиму посилення власних коливань напівпровідникових комплектуючих радіовиробів (зворотних відмов). Висновки. Кількісні оцінки режимів посилення (генерації) коливань напівпровідникових приладів, що спотворюють їх робочі характеристики залежно від параметрів зовнішнього електромагнітного впливу, дозволяє розробляти механізми електромагнітної сумісності радіовиробів НВЧ-діапазону. Порівняльний аналіз, отриманих у роботі розрахункових даних може бути використаний при виготовленні радіовиробів, що працюють у міліметровому та субміліметровому діапазоні (підсилювачів, генераторів та перетворювачів частоти).
Порушення власних коливання напівпровідникових комплектуючих радіовиробів при дії сторінного електромагнітного випромінювання
Keywords: induced current; electromagnetic pulse radiation; semiconductor components; surface oscillations; oscillation instability; наведений струм; електромагнітне імпульсне випромінювання; напівпровідникові комплектуючі; поверхневі коливання; нестійкість коливань